ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN KINERJA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN (ABANKIRENK Semarang) - Sudaryanto, Chandra Widi; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2017)
This  research  is  based  upon  the  appearance  of  competition  between  creative industry companies to win the market through accentuating quality that is given by every company within. The purpose of this research is to figure out the influence of product’s quality, quality of service, and company performance against customer satisfaction ( Abankirenk Semarang ).The result of research variable regarding product’s quality, quality of service, company performance against customer satisfaction (Y). The value of adjusted R square is 0,559. So that it can be concluded that the ability of all independent variables to explain the variation on dependant variable is 55,9% influential to Y variable. While the rest of 44,1% influential on other factor that is not explained in the regression model that is obtained.